Team Teaching During Field Experiences in Teacher Education: Investigating Student Teachers' Experiences With Parallel and Sequential Teaching. (January 2020) - Simons, Mathea; Baeten, Marlies; Vanhees, Claudio
During field experiences in teacher education, student teachers are generally placed individually with a mentor. Teacher education institutes search for alternative field experience models, inspired by collaborative learning such as team teaching. This study explores two team teaching models, parallel and sequential teaching, by investigating the student teachers' perspective. Quantitative (survey) and qualitative (self-report) methods were used to map their attitudes toward both models, their perception on collaboration, advantages and disadvantages, and the conditions for implementation they consider critical. Student teachers adopt positive feelings toward both models. In sequential teaching, collaboration is experienced significantly higher than in parallel teaching. Both models have their own advantages and disadvantages, but advantages clearly outweigh disadvantages. In comparison with previous research, decreased workload and better management are new advantages, interdependence and complex management new disadvantages. "Preparation for new roles" is the most important condition in order to successfully implement both models.